THE EFFECT OF CONSUMPTION OF BLACK CINCAU ICES ON REDUCING BLOOD PRESSURE IN PREGNANT WOMEN WITH HYPERTENSION - Arifin, Ahmad David Royyifi; Idcha Kusma Ristanti; Tiara Putri Ryandini (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Hypertension is a condition in which systolic blood pressure reaches or exceeds 140 mmHg and diastolic blood pressure reaches or exceeds 90 mmHg. The purpose of this study was to evaluate the effect of giving black grass jelly (Premna oblongifolia Merr) ice to pregnant women with hypertension. The method used in this study was a pre-experimental design with a One Group Pretest Posttest using a cross-sectional time approach. The research population consisted of 20 respondents, with a sample of 10 respondents selected using purposive sampling method. The results of this study concluded that giving black grass jelly ice has a positive effect, especially as an effective non-pharmacological method in reducing blood pressure in pregnant women who experience hypertension. These findings indicate that giving black grass jelly ice can be an effective alternative in managing blood pressure in pregnant women with hypertension. This method holds promise as an adjunctive therapy that can reduce the risk of complications related to hypertension in pregnant women.